School of Political Science - A. D. Voskresensky (Vestnik MGIMO-Universiteta)
Out of all the departments of political sciences in Russia - the Department at MGIMO-University is probably the oldest one. In fact it is very young. While MGIMO-University is celebrating its 70th anniversary the Department of Political Sciences turns 15. Despite the fact that political analyst is a relatively new profession in Russia, it acquired a legal standing only in the 1990s, the political science school at MGIMO-University is almost as old as the university itself. Unlike many other universities, focused on the training teachers of political science or campaign managers MGIMO-University has developed its own unique political science school of "full cycle", where students grow into political sciences from a zero level up to the highest qualifications as teachers and researchers, and campaign managers, consultants and practitioners. The uniqueness of the school of political science at MGIMO-University allows its institutional incarnation -the Department of Political Science - to offer prospective studentsa training in a wide range of popular specialties and specializations, while ensuring a deep theoretical and practical basis of the training. Studying at MGIMO-University traditionally includes enhanced linguistic component (at least two foreign languages). For students of international relations and political science learning foreign languages is particularly important.It allows not only to communicate, but also to produce expertise and knowledge in foreign languages.